PENINGKATAN MINAT DAN HASIL BELAJAR GEOGRAFI KONSEP PEDOSFER MELALUI STRATEGI PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK PADA SISWA KELAS X IPS 2 SMA NEGERI 1 MERANGIN - Yumilya Siska, S.Pd (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
The objectives of this CAR are: (a) To increase interest in learning geography on the Pedosphere concept, (b) To improve learning outcomes of Geography on the Pedosphere concept through a cooperative learning model of Group investigation type in class X IPS 2 SMAN 1 Merangin for the 2021/2022 school year. This PTK is done through 2 cycles. The data collected in this study consisted of quantitative data and qualitative data. Quantitative data obtained from test results were processed using percentage descriptions. The scores obtained by the students were averaged to find the level of understanding of the students' pedosphere concepts in learning Geography. Qualitative data obtained from observations and student questionnaires are classified based on the aspects that are the focus of the analysis. This quantitative and qualitative data is then linked as a basis for describing the successful application of the group investigation learning model which is characterized by an increase in student interest and learning outcomes in geography learning the pedosphere concept in classical geography learning. The results showed that the cooperative learning model of group investigation type that was applied to the Geography learning of the pedosphere concept was proven to increase student interest in learning both individually and classically, fostering the ability to work together, think critically, and at the same time there was also a significant increase in student learning outcomes. that is, from the average score of 59 students in the pre-cycle, it became 67.5 in the first cycle and increased to 71.77 in the second cycle. So that learning Geography of the pedosphere concept with the cooperative learning model of group investigation type is proven to be able to improve cognitive, affective and student psychomotor